Kepuasan Mahasiswa Terhadap Penempatan Magang Di Prodi Manajemen - Lila Maria Kaban; Daniel Cassa Augustinus (Journal of Accounting and Management Innovation, 2022)
Internship activities are carried out in universities to introduce the working world to students in the future. This is important to be examined, especially in terms of the effectiveness of the program that has been implemented. By conducting a survey of students who have undergone the internship process, a clearer picture can be obtained of overall student satisfaction in response to the placement process during the internship. There are five factors emerge from the data analysis, namely interpersonal skills, work environment, culture, challenges, and benefit.